Impact of Work Conditions and Minority Patient Populations on Quality and Errors - Anita B. Varkey MD; Linda Baier Manwell MS; Roger L. Brown PhD; Enid Montague PhD; Neda Laiteerapong MD; Diana Burgess PhD; Said Ibrahim MD (SAGE Publishing, 2016)
Objectives: To determine whether workplace conditions affect care quality and errors, especially in primary care clinics serving minority patients. Methods: We conducted a 3-year assessment of work conditions and patient outcomes in 73 primary care clinics in the upper Midwest and New York City. Study participants included 287 physicians and 1204 patients with hypertension and/or diabetes. Chart audit data were contrasted between clinics with ≥30% minority patients (minority-serving clinics, or MSCs) and those with <30% (nonminority-serving clinics, or NMSCs). Physicians reported on time pressure, work control, clinical resources, and specialty referral access; managers described room availability; and chart audits determined care errors and quality. Two-level hierarchical models tested work conditions as mediators between MSC status and clinical outcomes. Results: Error rates were higher in MSCs than NMSCs (29.6% vs 24.8%, P < .05). Lack of clinical resources explained 41% of the effect of MSC status on errors ( P < .05). Diabetes control was poorer in MSCs than in NMSCs (53.8% controlled vs 76.1%, P < .05); lack of clinical resources explained 24% of this difference ( P < .05). Room availability increased quality in both MSCs and NMSCs by 5.95% for each additional room per clinician per session. Lack of access to rooms and specialists decreased the likelihood of blood pressure control in MSCs. Conclusion: Work conditions such as clinical resources, examination room availability, and access to referrals are significantly associated with errors and quality, especially in MSCs.